THE MEANINGFULNESS OF LINGUISTIC EXPRESSIONS FROM THE TRUTH-CONDITIONAL THEORY OF MEANING (A METALINGUAL SYUDY) - Joko . Kusmanto; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2022)
Meaning is the essence of language. It has been one of the main concerns in the study of language since the age of Plato and Aristotle. There have been various theories of meaning but only a few explains ‘what one knows when s/he is said to know the meaning of linguistic expressions’. Truth-conditional theory of meaning is one of them – not to say the only theory of meaning – which explains ‘what one knows when s/he is said to know the meaning of linguistic expressions’. However, it has been little paid attention to by theorists working on linguistic meaning since the decline of the ideal language philosophy. It happens so because it is basically misunderstood, i.e. the misunderstanding between linguistic proposition and epistemic proposition in the correspondence theory of truth. This paper revives the significance of the truth-conditional theory of meaning in understanding what constitutes the meaning of linguistic expressions when one is said to know it.